Management of Severe Trismus with Bilateral Recurrent Pericoronitis alongwith Chronic Oral Submucous Fibrosis - A Case Report - Nanda Kishore Ghoshal (Journal of Orofacial Research, 2021)
A 37 years, old male patient reported with the chief complaint of inability to open mouth since 10-11 months and recently pain and swelling resulting from wisdom teeth of both sides limited the mouth opening severely (<9mm, less than one finger opening) that he could not take solid food properly. After partial relief and mouth opening (12mm) with antibiotic therapy patient was examined and diagnosed as oral submucous fibrosis (osmf) along with impacted molars in both sides. Treatment was planned with conservative approach consisted of pharmacotherapy and physiotherapy for osmf and surgical removal of impacted third molars of both sides. Mouth opening was improved gradually (>15mm after 3 weeks, >22mm after 6 weeks,>27 mm after 9 weeks).